Estimulación temprana y el lenguaje oral en niños de tres años de la Institución Educativa Inicial Unap Maria Reiche, San Juan 2022 - Diaz Ramirez de Zambrano, Etna (2024)
The main objective of this research was to establish the link between early stimulation and the development of oral language in three-year-old children of the UNAP María Reiche Initial Educational Institution, located in San Juan, during the year 2022. The study was framed within the correlational and transectional approach, adopting a non-experimental design. The population was made up of 57 parents and 57 three-year-old children from said institution, selected through census sampling. In this context, it was considered essential to use observation and an observation sheet as tools to collect data. The validation of these instruments was carried out by three specialists with experience in the topics addressed by the research. The findings, the Kendall rating coefficient (Tau_b) between early stimulation and oral language was 0.367, with a bilateral significance of 0.040, suggesting a positive and statistically significant relationship between both variables. Similarly, Spearman's rating coefficient reached a value of 0.334, also with a two-sided significance of 0.040, similarly reflecting positive compensation. In conclusion, it is established that there is no significant relationship between both words.